2018
DOI: 10.1182/blood-2018-99-119352
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in Iron Deficiency Anemia

Abstract: Background: Thrombocytosis can be a result of a reactive process such as acute blood loss, infections, iron deficiency anemia (IDA) or a clonal disorder such as Essential Thrombocythemia. The challenge of correctly identifying the etiology of thrombocytosis in an individual patient becomes particularly essential when the clinician is confronted with decisions regarding further workup, follow up as well as preventing future complications such as thrombotic events. Prior data linking iron deficiency anemia and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Unlike the earlier profiles, there was no significant difference in the patients’ ages, sex or clinical features for the combined iron and clotting profiles. The Profile 1 combination of lowest iron, T f SI and ferritin with highest platelet count is reminiscent of the data that thrombocytosis accompanies acute haemorrhage with iron deficiency anaemia shown to be associated with higher platelet counts [37,38]. Of note, within the combined iron and clotting profiles, all SMAD4 patients were within the iron‐deficient profile.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Unlike the earlier profiles, there was no significant difference in the patients’ ages, sex or clinical features for the combined iron and clotting profiles. The Profile 1 combination of lowest iron, T f SI and ferritin with highest platelet count is reminiscent of the data that thrombocytosis accompanies acute haemorrhage with iron deficiency anaemia shown to be associated with higher platelet counts [37,38]. Of note, within the combined iron and clotting profiles, all SMAD4 patients were within the iron‐deficient profile.…”
Section: Resultsmentioning
confidence: 77%
“…Clotting indices comprised platelet count, serum fibrinogen concentration, prothrombin time (PT) and activated partial thromboplastin time (APTT). Iron indices included serum iron, T f SI, ferritin and C‐reactive protein (CRP) as a known confounder (marker of inflammation that increases serum ferritin) [27, 37, 38].…”
Section: Methodsmentioning
confidence: 99%
“…Since disease-related blood loss can be encountered in OSCC, CRT can be immunosuppressive, inhibiting erythropoiesis and gastrointestinal mucositis, resulting in further nutritional status deterioration. Chronic malnutrition may strengthen anemia severity, such as via folic acid and iron insufficiency [ 40 ]; this may also be partly caused by alcohol consumption in most of our patients. Consistent with a previous study [ 10 , 36 ], sarcopenia may be a more accurate marker for nutritional status than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that PLR was a predictor of CIA. Thrombocytosis can result from reactive processes such as acute blood loss, infections, and iron deficiency anemia [ 40 , 41 ]. However, further research is still required to show an effect between PLR and the cause of anemia during CRT in patients with OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytosis was associated with severe anemia in 32.7% of children in the present study. This is explained by reactive thrombocytosis to iron deficiency anemia where erythropoietin stimulates thrombopoietin receptors and thus megakaryocytes [15].…”
Section: Kayalvizhi Et Almentioning
confidence: 99%